PENYULUHAN TENTANG ALUR PELAYANAN BEROBAT DI RUMAH SAKIT KEPADA MASYARAKAT KELURAHAN PEBATUAN KECAMATAN TENAYAN RAYA TAHUN 2021 - Marian Tonis; Muhammad Firdaus; Shelly Angella; Aulia Annisa (Awal Bros Journal of Community Development, 2021)
Most of the people in the Pebatuan village are still confused about the flow of services at the hospital due to the lack of information related to this. This causes some people to be lazy to go to the hospital for reasons of difficult process and others. Therefore, the holding of outreach activities related to the flow of services in the hospital starting from the patient entering, then registration, action, inpatient or outpatient, pharmacies, cashiers until the patient goes home. because the process is difficult and so on. The method of community service is by distributing brochures, lectures, and discussions as well as answering questions. This community service was carried out in the Pebatuan Village, Tenayan Raya District, held on Wednesday, February 24, 2021. The implementation starts from the opening and greetings from the presenter, then the presentation of material by the resource person, the question and answer session and discussion is then closed by saying greetings. This community service is important for the community to provide clear information regarding the flow of services in the hospital, and it is important for people whose cultural customs are still strong.